Do grassroots interventions relax behavioural constraints and improve adoption of nutrition-sensitive food production systems? - Alvi, Muzna; Ward, Patrick S.; Makhija, Simrin; Spielman, David J. (Wiley, 2024)
In most developing countries, agricultural policies and programs are designed to promote productivity growth with modern inputs and technologies, and the success of these policies is measured primarily along the dimensions of technology adoption, with limited reference to the ancillary impacts on behavioural outcomes that may be a prerequisite to adoption. We test whether grassroots programs can additionally relax behavioural constraints, potentially enhancing the adoption of diversified production systems. In Odisha, India, using a series of laboratory‐in‐field experiments and survey instruments to elicit farmers' preferences for risk, agency and aspirations for themselves and their children, we find that respondents in villages where grassroots interventions were promoted showed significantly lower levels of risk aversion and higher aspirations for themselves and their children, along with improvements in production and consumption diversity. However, we do not find a mediating role of reduced risk aversion in improving direct program outcomes. Our results show that grassroots approaches are effective in inducing a shift towards changing production systems, and relaxing behavioural constraints, that can be leveraged over time to strengthen impacts.